Isolation of two basic phospholipases A2 from Bothrops diporus snake venom : comparative characterization and synergism between Asp49 and Lys49 variants - Bustillo, Soledad (2019)
Fil: Bustillo, Soledad. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.